Capítulo 3 — Evaluación de los árboles dañados durante un huracán y toma de decisiones - Eliana Kampf; Mary L. Duryea; Edward F. Gilman; Astrid Delgado (EDIS)
FOR-117-Sp, a 17-page, full-color fact sheet by Eliana Kampf, Mary L. Duryea, Edward F. Gilman, and Astrid Delgado, is the Spanish language version of FOR-117, Chapter 3 - Assessing Hurricane-Damaged Trees and Deciding What to Do. It is part of the Urban Forest Hurricane Recovery Program series. It discusses factors that should be considered when deciding whether to remove or restore storm-damaged trees.  Published by the UF School of Forest Resources and Conservation, January 2007.